Healthful and Unhealthful Provegetarian Food Patterns and the Incidence of Overweight/obesity in the Seguimiento Universidad De Navarra (SUN) Cohort (OR33-05-19) - Gómez-Donoso, Clara (Curr Dev Nutr, 2019)
OBJECTIVES: Provegetarian diets (i.e., preference for plant-derived foods) have been associated with a reduced risk of long-term weight gain and could be more easily embraced than strict vegetarian diets. However, not all plant-derived foods are equally healthy. The objective was to identify the association between provegetarian food patterns and the incidence of overweight/obesity. METHODS: The analysis included 11,554 participants with a baseline BMI < 25 kg/m(2) from the SUN (Seguimiento Universidad de Navarra/University of Navarra Follow-up) prospective, open-recruitment cohort. Food consumption was assessed using a 136-item validated food-frequency questionnaire. A provegetarian food pattern (FP) was built by assigning positive scores to plant foods and reverse scores to animal foods as proposed by Martínez-González et al (2014). We also created a healthful provegetarian FP where healthy plant foods (fruits, vegetables, whole grains, nuts, legumes and olive oil) were positively weighted but less-healthy plant foods (juices, potatoes, refined grains, pastries and other vegetable oils) and animal foods were negatively weighted. To build an unhealthful provegetarian FP, less-healthy plant foods were positively weighted and animal and healthy plant foods were negatively weighted as suggested by Satija et al (2017). Participants were categorized into energy-adjusted quintiles of the different versions of a provegetarian FP. We calculated adjusted hazard ratios (HR) of overweight/obesity (BMI ≥ 25 kg/m(2)) and their 95% confidence intervals (CI). RESULTS: A total of 2320 new cases of overweight or obesity were identified after a median follow-up of 10.3 years. Higher baseline conformity with the overall provegetarian FP was inversely associated with overweight/obesity (multivariable-adjusted HR comparing extreme quintiles: 0.86; 95% CI: 0.74, 0.99; P-trend: 0.061). This inverse association was stronger for the healthful version (HR: 0.82; 95% CI: 0.72, 0.95; p trend: 0.001) and was not apparent for the unhealthful version (HR: 1.07; 95% CI: 0.94, 1.23; p trend: 0.363). CONCLUSIONS: Among relatively young graduates, better conformity with a healthy provegetarian diet was associated with a reduced risk of overweight/obesity, whereas no consistent trend was found for a FP that emphasized less-healthy plant foods. FUNDING SOURCES: The SUN Project has been supported by the Institute of Health Carlos III, the European Regional Development Fund, the Navarra Regional Government, and the University of Navarra. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: